Self-assembled hyaluronic acid nanoparticles: Implications as a nanomedicine for treatment of type 2 diabetes - Rho, Jun Gi; Han, Hwa Seung; Han, Ji Hye; Lee, Hansang; Nguyen, Van Quy; Lee, Wang Hee; Kwon, Seunglee; Heo, Sungeun; Yoon, Juhwan; Shin, Han Ho; Lee, Eun young; Kang, Hoin; et al. (Journal of Controlled Release, 2018)
Self-assembled hyaluronic acid nanoparticles (HA-NPs) have been extensively investigated for biomedical and pharmaceutical applications owing to their biocompatibility and receptor-binding properties. Here, we report that an empty HA-NP itself not bearing any drug has therapeutic effects on adipose tissue inflammation and insulin resistance. HA-NPs inhibited not only the receptor-mediated internalization of low-molecular-weight (LMW) free HA but also LMW free HA-induced pro-inflammatory gene expression in mouse primary bone marrow-derived macrophages (BMDMs) isolated from wild-type mice, but not in CD44-null (CD44−/−) BMDMs. An in vivo biodistribution study showed the distribution of HA-NPs and their co-localization with CD44 in adipose tissues including epididymal white adipose tissues (eWATs), but these were rarely observed in the eWATs of CD44−/− mice. In addition, CD44 expression and HA-NP accumulation in the eWATs were increased in mice with diet-induced obesity (DIO) compared to lean mice. Interestingly, treatment with HA-NPs in DIO mice suppressed adipose tissue inflammation as indicated by reduced macrophage content, the production of proinflammatory cytokines and NLRP3 inflammasome activity in eWATs, leading to improved insulin sensitivity and normalized blood glucose levels. Collectively, these results suggest that an empty HA-NP itself can be a therapeutic agent for the treatment of type 2 diabetes.
Keywords: Inflammation; Inflammatory gene expressions; Insulin resistance; Pharmaceutical applications; Pro-inflammatory cytokines; Self assembled nanoparticles; Type-2 diabetes; White adipose tissues; Adipose Tissue; Animals; Blood Glucose; Cytokines; Diabetes Mellitus, Type 2; Hyaluronan Receptors; Hyaluronic Acid; Inflammation; Insulin Resistance; Macrophages; Male; Mice; Mice, Inbred C57BL; Mice, Inbred DBA; Mice, Knockout; Nanomedicine; Nanoparticles; Obesity; Tissue Distribution; Hyaluronic acid; Inflammation; Insulin resistance; Nanomedicine; Self-assembled nanoparticles; Type 2 diabetes